A Comparison of Two Initial Eligibility Rules: Proposition 48 and 16 - Zangari, Ronald E. (My University, 1995)
Two NCAA initial eligibility rules were compared to determine which was more restrictive in terms of the overall number of studnet-athlete sdelcared ineligible to compete and which was more accurate in identifying future graduates. The sample consisteted of 164 freshman student-athletes enrolled at Clarion Univeristy of PA (DIvision II except Division I in wrestling) in 1989. A standard decision table was employed to classify the subjects. The variables studied included high school core GPA, precollege test scores, equally weighted average of GPA and test z-scores, and graduation within a five year period). Athletes who transferred, continued beyond five years, or left in good academic standing were all considered dropouts. Results found Proposition 16, which will be implemented in 1996, to be significantly more resitrctive than Proposition 48, the current rule. The new rule also rejected significantly more future graduates than the current rule, but no other statistically signifcant results were obtained.
Keywords: eligibility; Division II; Division I